New York Cosmopolis Episode 5 & City of Tomorrow Episode 6 - Burns, Ric. (USA 2004)
If you are interested in a thorough but entertaining history of New York City this is as good as it gets. Ric Burns provides plenty of details but doesn't forget that part of the reason viewers are watching is to have some fun too. Eight DVDS may seem like too much but with a city like New York it is surprising how quickly the show passes by, this collection is large enough to give you a serious history of the topic without getting too complicated. If you are looking for a travel guide to NYC this isn't for you, if you are a sports fan look elsewhere, don't expect a guide to theatre or restaurants either. This DVD set is meant as a visual history course of America's, if not the world's, most fascinating city.
Language(s): English Subtitle(s): No Subtitles
Keywords: History